Simulated measurement-uncertainty determination for mass-standard calibration via transfer artefacts. (December 2021) - Härtig, Frank; Lehrmann, Katharina; Tutsch, Rainer
Abstract: Monte Carlo methods are appropriate for determining manufacturing accuracy or measurement uncertainty for the calibration of mass standards such as sorption, duplex and buoyancy artefacts, which are referred to as transfer artefacts . Systematic influences and their application-specific measurement uncertainties can be calculated for three important parameters: mass, surface area and volume. The input variables of the simulations yield from the specified manufacturing tolerances as well as from the measurement uncertainties associated with the input variables related to the coordinate measuring machines employed. The model developed here allows the transfer artefacts shown to be calculated with a uniform approach in accordance with the specifications of GUM. Results for silicon transfer artefacts with a nominal mass of 1 kg are presented and discussed.